2016
DOI: 10.17221/270/2016-pse
|View full text |Cite
|
Sign up to set email alerts
|

Meat and bone meal as fertilizer for spring barley

Abstract: The aim of this study was to determine whether meat and bone meal (MBM) can be used as NP fertilizer for spring barley grown for fodder. A two-factorial field experiment was conducted in Poland. Experimental factor I was MBM dose (0, 1.0, 1.5, 2.0, 2.5 t/ha/year) which was compared to the mineral fertilization (NPK), factor II was the year of the study (two consecutive years). MBM used in doses higher than 1.0 t/ha had a more beneficial influence on the grain yield of spring barley and grain plumpness than min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 11 publications
(14 reference statements)
1
14
0
Order By: Relevance
“…In addition, the N and P balance in soil and N and P utilization by the crops were calculated. The results pertaining to grain yield and quality and NP uptake were reported in earlier studies (Nogalska et al 2012, Nogalska 2016.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, the N and P balance in soil and N and P utilization by the crops were calculated. The results pertaining to grain yield and quality and NP uptake were reported in earlier studies (Nogalska et al 2012, Nogalska 2016.…”
Section: Introductionmentioning
confidence: 57%
“…The highest abundance of mineral N in soil in the second year of the study most probably resulted from the lowest N uptake by spring barley (over two-fold lower compared with the first and third year). In the first year (2011), N uptake by maize was 183.5 kg ha -1 on average (Nogalska et al 2012), whereas in 2012 and 2013, N uptake by spring barley was 83.5 and 174.7 kg ha -1 , respectively (Nogalska 2016).…”
Section: Resultsmentioning
confidence: 99%
“…White mustard yields in the treatment with the medium MBM rate (0.4%) and in the control treatment were comparable, and the amount of supplemental N was identical in both treatments (3.0 g pot -1 ). A beneficial influence of MBM on crop yields has been reported by many authors (Jeng et al 2004, Chaves et al 2005, Ylivainio et al 2008, Nogalska 2016. In the present study, MBM was incorporated into the soil at a single rate before sowing, whereas mineral fertilizer (CO[NH 2 ] 2 ) -46% N was applied at 1.5 g N pot -1 per growing season at three equal rates of 0.5 g each.…”
Section: Plant Yieldmentioning
confidence: 74%
“…700 g kg -1 DM) (Jeng et al 2006). MBM contributes to soil fertility, higher yields and better quality of agricultural products (Jeng et al 2004, Chaves et al 2005, Jeng et al 2006, Brod et al 2012, Nogalska and Zalewska 2013, Nogalska 2016, Nogalska et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that N compounds account for only 80 g kg −1 of the MBM and that mineral N accounts for only a minor portion of total N, the low C:N ratio of MBM (approximately 4) provides great potential for N mineralization [3]. Numerous studies have shown that MBM contributes to soil fertility, higher crop yields, and better quality of agricultural produce [1,4,[7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%